(untitled) (Scottish Historical and Archaeological Internet Reports, 2006)
The presence of the bead and the crucible with its implications of bronze working on the site suggest that in the 1st-2nd centuries AD the site was either part of a settlement of some standing, or perhaps related to, or peripheral to a high-status settlement.